Strengthening Student Literacy through Mandatory KIR Program: Evidence from Principal Leadership Practices - Sugiyanti Sugiyanti; Ngurah Ayu Nyoman Murniati; Bunyamin Bunyamin (FKIP - Universitas Riau, 2026)
Strengthening students’ literacy has become an important issue in improving educational quality through school-based academic programs that foster critical thinking and scientific literacy. This study aims to analyze the principal’s leadership practices in implementing a literacy strengthening program through the mandatory Youth Scientific Writing (Karya Ilmiah Remaja/KIR) program at SMA Negeri 1 Rembang. A qualitative case study design was employed. Data were collected through interviews, observations, and documentation involving the principal, teachers, students, and parents. Data were analyzed using data reduction, data display, and conclusion drawing techniques. The analysis generated four major themes: evaluation strategies, corrective mechanisms, literacy development impacts, and principal involvement in program sustainability. The findings show that the principal institutionalized the KIR program through routine evaluation meetings, integration of KIR outcomes into academic assessment, and collaborative communication with teachers and parents. Corrective actions included strengthening mentoring, improving supervision coordination, and addressing implementation barriers. Data also revealed changes in students’ literacy-related behaviors, including increased engagement in reading references, scientific discussions, report writing, and independent learning activities. The study concludes that transformational leadership, continuous evaluation, and collaborative support are essential for strengthening a sustainable school literacy culture through scientific writing programs.